New molecular therapies in patients with advanced Hepatocellular Cancer in second line of treatment: Is a real defeat?: Results from a literature based meta-analysis of randomized trials. (December 2016) - Roviello, Giandomenico; Zanotti, Laura; Cappelletti, Maria Rosa; Gobbi, Angela; Borsella, Giulia; Pacifico, Chiara; Multari, Andrea Giovanni; Generali, Daniele
Highlights: Effective treatments after sorafenib therapy remain an unmet medical need. The considered secondary end-points such as PFS and response favoured the use of target agents in the second line of treatment of advanced HCC. The incidence of a grade ≥3 adverse event was higher in the arm with molecular therapies. Abstract: Several new biological agents have been investigated as second line of treatment in advanced Hepatocellular Cancer (HCC). We performed a meta -analysis to assess the effect of targeted therapies in advanced HCC patients beyond the first line of treatment. A literature-based metaanalysis of randomized controlled trials was undertaken. The primary outcome was the overall survival. The secondary endpoints were the progression-free survival (PFS), the response rate (RR) and disease control rate (DCR) and the safety. Pooled analysis of targeted agents revealed a modest increase in overall survival compared with control arm (Hazard Ratio (HR) = 0.93, 95%CI: 0.83-1.04; P = 0.21). On the counterpart, all the secondary endpoints were in favoured to the targeted agents-based treatment (PFS: HR = 0.68, 95% CI:0.56–0.83; P = 0.0002; RR: 3.50, 95% CI 1.81–6.76; P = 0.0002, DCR: RR:1.19, 95% CI 1.06–1.32; P = 0.002). To date, there is a clinical need of a more efficacious second line of therapy in treatment of the advanced HCC. This study showed some activity of the new targeted therapies in second line of treatment in advanced HCC.